A WeChat-Based System of Real-Time Monitoring and Alarming for Power Grid Operation Status under Virtual Private Cloud Environment. (7th March 2020) - Lian, Chunjie; Wei, Hua; Bai, Xiaoqing; Lyu, Zhongliang
Abstract : The existing power grid alarm system using SMS (SMSAS) is complex and suffers some problems such as high latency in data transmission, low reliability, and poor economy. For solving these problems, this paper proposes a WeChat-based system under the virtual private cloud environment to achieve real-time monitoring and alarming for the power grid operation status (WMAS). For WMAS, the WeChat mini program (WMP) is adopted, and it has the dedicated data channel using the Https protocol, which is set up in the WMP and the web API to encrypt the data content to ensure the integrity of the data. Combined with virtual private cloud technology, the hardware resources are virtualized, and the proposed system has strong disaster recovery capability, which significantly improves the flexibility and reliability of the system. Compared with SMSAS, our simulation shows that the time from sending to receiving the information in the proposed system is reduced from 4.9 seconds to 172 milliseconds, with the latency reduced by 28 times. On the contrary, the reliability of the proposed system is as high as 99.9971%, and the annual failure time is 15.24 minutes, which is 380 times lower than 96.51 hours of the SMSAS. The proposed system has been implemented in the Lipu power system in Guangxi, China. More than one year of stable operation indicates that the proposed system is safe, reliable, flexible, and convenient with a bright prospect for future applications.